2012
DOI: 10.1007/s00417-012-1944-5
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition of human lens epithelial cells by short hairpin RNA in transcription factor forkhead box E3 (FOXE3)

Abstract: shRNA-mediated gene silencing of FOXE3 could significantly inhibit cell growth and induce the G1-phase arrest in HLEB-3 cells. Formation of posterior capsular opacification might be repressed if lens epithelial cell growth ceases after the FOXE3 gene is silenced with molecular biology technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…We repeated the luciferase reporter assay in HLE cells to reproduce the results in a physiologically relevant system. The expression of wild-type FOXE3 caused significant alteration in shape and eventually death in HLE cells, consistent with previously published reports of ectopic expression of Foxe3 in the mouse lens 20 21 .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We repeated the luciferase reporter assay in HLE cells to reproduce the results in a physiologically relevant system. The expression of wild-type FOXE3 caused significant alteration in shape and eventually death in HLE cells, consistent with previously published reports of ectopic expression of Foxe3 in the mouse lens 20 21 .…”
Section: Resultssupporting
confidence: 91%
“…However, Wang et al . 20 previously reported that short-hairpin RNA (shRNA)-mediated silencing of FOXE3 significantly inhibits cell growth and induces G1-phase arrest in cultured HLE cells. Therefore, to preclude the possibility of confounding experimental interpretation, we opted to use cell lines negative for endogenous FOXE3 expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cells were treated with miR-204-5p antagomir, and the MTT assay was used to determine relative cell growth as described previously. 21 Data from the MTT colorimetric assay are shown in Figure 4. The absorbances were 0.940 6 0.028, 0.841 6 0.067, 0.258 6 0.051, 0.412 6 0.032, and 0.845 6 0.008 in the NG, HM, HG, HG plus miR-204-5p antagomir NTC, and HG plus miR-204-5p antagomir groups, respectively (n ¼ 3 for each group).…”
Section: Downregulation Of Mir-204-5p Increases Tke2 Cell Growth Resmentioning
confidence: 99%